Development of Blumlein Line Generator and Reactor for Wastewater Treatment - Zainuddin Nawawi; Muhammad Abu Bakar Sidik; Zolkafle Buntat; S. M. Zafar Iqbal; Hashem Ahmadi; Muhammadjavad Mobarra (Universitas Ahmad Dahlan, 2013)
There are several wastewater treatment methods and techniques which have been introduced such as by using biological, chemical, and physical process. However, it is found that there are some shortcomings in the current available methods and techniques. For instance, the application of chlorine can cause bacterial disinfection but produce secondary harmful carcinogenic disinfection. In order to acquire a better understanding in wastewater treatment process, a study of wastewater treatment system and hybrid discharge reactor to acquire gas liquid phase corona like discharge is carried out. In addition to the laboratory experiment, designing and development of the Blumlein pulse power circuit and modification of reactor for wastewater treatment are accomplished as well. The Blumlein pulse power circuit generates nanosecond high voltage pulses. The Hybrid Discharge reactor can produce both spark discharge in gas phase and liquid phase (spark-spark discharge). Analysis of the emission spectrum of the occurring discharge found the existence of various chemicals such as OH radicals. In addition, a drastic improvement in terms of oxygen content and conductivity level of the wastewater sample is also observed.